(untitled) (Scientific journal of the Fergana State University, 2026)
In this article, the issue of guiding the younger generation toward perfection based on the philosophical and moral heritage of Fazl ibn Ahmad is analyzed. According to the author, relying on national and Islamic heritage plays a crucial role in educating the youth of New Uzbekistan as spiritually mature and morally upright individuals. From this point of view, Fazl ibn Ahmad’s teachings on the human soul, the balance between reason and heart, moral perfection, and enlightenment serve as a spiritual and moral program for today’s youth. His philosophy emphasizes the ideas of self-discipline, attaining perfection through knowledge, and serving the interests of society. The study and integration of Fazl ibn Ahmad’s legacy into the educational and upbringing processes strengthen the sense of patriotism, spiritual integrity, and social responsibility among young people. Therefore, this heritage holds special significance as an integral part of the spiritual policy of New Uzbekistan.